Arbetsrelaterad stress bland klientnära socialarbetare - Esber Daoud,Mikael; Murtic,Edvin (2025)
This study examines how client-facing social workers experience work-related stress and how it affects their motivation and engagement in their jobs. Social work often includes high demands, emotional challenges, and limited resources, which can lead to stress and exhaustion. At the same time, many social workers remain motivated and committed to their work, which makes it important to understand what helps them cope. The study is based on six interviews with social workers from different areas, such as LSS (Law of Support and Service), SIS (The Swedish National Board of Institutional Care), HVB (home care or residence), and domestic service. A thematic analysis was used to identify common experiences and patterns related to work-related stress and its impact on motivation and engagement among client-facing social workers. The analysis was supported by three theories: Karasek’s demand–control Theory (Krav Kontroll), Social Support Theory, the buffering hypothesis (social support theory), and Self-Determination Theory (SDT). The results show that high workload, poor staffing, and lack of control over the work situation are major sources of stress. However, motivation often remains strong when the work feels meaningful, especially in close contact with clients. Support from colleagues and managers, opportunities to make their own decisions, and a feeling of doing something important were described as helpful in handling stress. The study highlights the importance of creating work environments that offer enough support, flexibility, and appreciation. By understanding what increases stress and what helps reduce it, employers can create better conditions for social workers to stay healthy, motivated, and engaged over time.
Keywords: work-related stress; client-facing social workers; motivation; engagement; burnout work environment